Sweden : Financial Sector Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2011)
The impact of the financial crisis on Sweden's economy and financial sector is analyzed in this study. From the financial stability analysis, banks are resilient to credit risk and could face difficulties with respect to liquidity risk. The frameworks of international reserve management and Riksbanken's (RB's) are reviewed by authorities. The existing framework is augmented by the high-level systemic financial stability council (SFSC) to coordinate financial stability policies and actions. The authorities will strengthen the Finansinspektionen (FI)'s resources and legal frameworks for bank resolution and security markets.